Perceptions of Doing Business in Other Countries: A Logistic Regression Analysis of Survey Results - Gloria Fragoso-Diaz (International Journal of Supply Chain Management, 2015)
Abstract -This study involved an analysis of survey results about perception of doing business. U.S. Manufacturing managers were asked about their opinion on the Ease of Doing Business indicators with respect to Mexico, India, China and Singapore. The purpose of this research is to find out about the managers perceptions and determine from a set of give factors which are significant to the opinion. Logistic regression was used. Regressors used include demographics such as age, have lived abroad and have experience with outsourcing. Competitive priorities such cost, quality, delivery and flexibility and challenging to offshoring diverse functions were also used. Lastly comparative analyses of score were done with the World Bank ranking of economies. Experience with outsourcing resulted in a significant variable and flexibility and cost were significant to China. Quality and delivery were significant to Singapore in terms of Trading Across the Border. Perception of how challenging to outsource is assembly resulted significant to china in terms of business indicators: Time to Open a Business and Trading Across Border. Finally, a comparative analysis with the World Bank rankings displays a gap between perception and reality.